The effects of preventative cannabidiol in a male neuregulin 1 mouse model of schizophrenia - Visini, Gabriela; Brown, Samara; Weston-Green, Katrina; Shannon Weickert, Cynthia; Chesworth, Rose; Karl, Tim (Frontiers in Cellular Neuroscience, 2022)
Cannabidiol (CBD) is a non-intoxicating cannabinoid with antipsychotic-like properties, however its potential to prevent schizophrenia development has not been thoroughly investigated. Brain maturation during adolescence creates a window where CBD could potentially limit the development of schizophrenia. The Nrg1 transmembrane domain heterozygous (Nrg1 TM HET) mutant mouse shows face, predictive, and construct validity for schizophrenia. Here we sought to determine if CBD given in adolescence could prevent the development of the schizophrenia-relevant phenotype, as well as susceptibility to the psychoactive cannabinoid Δ⁹-tetrahydrocannabinol (THC) in Nrg1 TM HET mice. Adolescent male Nrg1 mutants and wild type-like (WT) animals were administered 30 mg/kg CBD i.p. daily for seven weeks, and were tested for locomotion, social behaviour, sensorimotor gating and cognition, and sensitivity to acute THC-induced behaviours. GAD67, GluA1, and NMDAR1 protein levels were measured in the hippocampus, striatum, and prefrontal cortex. Chronic adolescent CBD increased locomotion in animals regardless of genotype, was anxiolytic, and increased social behaviour when animals were tested in the THC battery. CBD did not alleviate the schizophrenia-relevant hyperlocomotive phenotype of Nrg1 mutants, nor deficits in social behaviours. Nrg1 mutant mice treated with CBD and THC showed no habituation to a startle pulse, suggesting CBD increased vulnerability to the startle habituation-reducing effects of THC in mutant mice. CBD increased levels of GluA1, but reduced levels of GAD67 in the hippocampus of Nrg1 mutants. These results suggest adolescent CBD is not effective as a preventative of schizophrenia-relevant behavioural deficits in mutants and may actually contribute to pathological changes in the brain that increase sensitivity to THC in particular behavioural domain.